Biobutanol Production Using High Cell Density Fermentation in a Large Extractant Volume - Rizki Fitria Darmayanti; Yukihiro Tashiro; Kenji Sakai; Kenji Sanomoto; Ari Susanti; Bekti Palupi; Meta Fitri Rizkiana (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
Biobutanol is well known as a suitable substitute for gasoline, which can be applied without engine modification. Butanol toxicity to the producer strain causes difficulties to grow strain of higher than 4 g/L dry cell weight and to produce butanol higher than 20 g/L. Fermentation using high initial cell density has been reported to enhance butanol productivity. In addition, oleyl alcohol has been recognized for effective extraction of butanol because of its selectivity and biocompatibility with reduced the effect of toxicity. Butanol fermentation with high cell density and large extractant volume has not been reported and is expected to improve butanol production in a minimum medium volume setting. Clostridium saccharoperbutylacetonicum N1-4, C. beijerinckii NCIMB 8052 (8052), and C. acetobutylicum ATCC 824 (824) were used in this study. Three kinds of media, TYA, TY, and TY-CaCO3, were used in this conventional extractive fermentation. Then, in situ extractive fermentation with Ve/Vb ratios at 0.1, 0.5, 1.0, and 10 were used. Total butanol concentration was defined as the broth-based total butanol, which is the total amount of butanol produced in broth and extractant per the volume of broth. TYA medium yielded the highest total butanol concentrations at N1-4 (12 g/L), 8052 (11 g/L), and 824 (15 g/L), and the highest partition coefficient (3.7) among the three media with similar Ve/Vb ratio at 0.5. N1-4 yielded the highest increment of total butanol production (22 g/L) in the extractive fermentation with high cell density. Low butanol concentration of 0.8 g/L in the broth was maintained using the extractant at a broth volume ratio (Ve/Vb) much lower than 4.4 g/L with a ratio of 0.5. Ve/Vb ratio of 10 which provided 2-fold higher total butanol concentration (28 g/L) than that of 11 g/L obtained using a Ve/Vb ratio of 0.5. These results indicated that a larger volume of extractant to broth improved total butanol concentration by reducing butanol toxicity and led to high medium based butanol yield in fermentation using high cell density.